Calciphylaxis-as a drug induced adverse event. Issue 1 (2nd January 2019) - Portales-Castillo, Ignacio; Kroshinsky, Daniela; Malhotra, Cindy K.; Culber-Costley, Roberta; Cozzolino, Mario Gennaro; Karparis, Shelly; Halasz, Charles L.; Goverman, Jeremy; Manley, Harold J.; Malhotra, Rajeev; Nigwekar, Sagar U.
ABSTRACT: Introduction : Calciphylaxis is a rare but devastating disease with a mortality rate up to 50% in 1 year. It is characterized by profoundly painful ischemic skin lesions and vascular calcification that affects predominantly patients with end stage renal disease. The use of certain medications is an important modifiable risk factor in calciphylaxis and discontinuation of these is a mainstay of treatment. Areas covered : This review will provide an overview of calciphylaxis and will focus on how certain therapeutic agents can affect the risk of calcification and associated thrombosis, key processes involved in the development of calciphylaxis. Expert opinion : Calciphylaxis treatment requires a multi-modal approach including prevention, risk factor management, wound care, reperfusion, and use of fibrinolytics and antioxidants. Patients with end stage renal disease represent the most affected population. This population often has multiple medications prescribed, some worth reconsidering before starting or continuing them. When possible, we recommend stopping all potentially contributing medications in patients with calciphylaxis, including warfarin, active vitamin D, calcium supplements, and iron. Trial registration: ClinicalTrials.gov identifier: NCT02278692.